THE DEVELOPMENT OF AN ITEM BANK OF WORD PROBLEMS TO MONITOR PROGRESS OF STUDENTS WITH LEARNING DIFFICULTIES IN MATHEMATICS (Proceedings of International Conference on Special Education, 2023)
As children progress from preschool to primary school, the content of mathematics learning gains more depth and an emphasis on problem solving is one of the core processes in the mathematics curriculum. Word problems are accorded such significance as the problem solving skills involve the development of other life skills such as communication and reasoning. Students with difficulties in mathematics often encounter difficulties solving word problems.  Prior to intervention in supporting students, an item bank of word problems with different levels of difficulty should be developed. This allows for word problems of similar difficulties to be administered to monitor the progress. In addition, the difficulty level of the word problems in the item bank could also inform teachers of the potential difficulty level of the word problems that could affect their students’ performance. In order to develop the item bank of word problems, the word problem type of combine, change and compare were administered to 191 students in Primary 3. Using their performance in the word problems, the Rasch model of measurement was used to analyze the data to determine the difficulty level of the word problems. There were 75 word problems administered and the difficulty level of the word problems ranged from most difficult word problem at 5.58 logit while the easiest was -4.92 logit. Among the three types of word problems, the Change Word Problem had the widest range of difficult and less difficult word problems. The difficulty level of the word problems enables word problems of varying difficulties to be included at baseline and also during intervention to monitor students’ progress during intervention.